TOWARDS NON-PLACE. THINKING IN TERMS OF SPACE IN ÁDÁM BODOR’S WORLD - Piotrowiak-Junkiert, Kinga (Porównania, 2012)
The article presents an analysis of the spatial conception in the works of Ádam Bodor (The Sinistra Zone, The Archbishop visit). The construction of the novels written by the Hungarian writer depicts that in this novel there appears a particular story space. Bodor describes places, which didn’t exist in external reality. He also gives them names which constitute a type of hint. The readership can easily decode the names of the borderlands. The writer constructs these ideas based on his own philosophy which is connected with perturbations of the cyclical processes of nature, metaphors of the totalitarian world but also being the eternal Wanderer.